Measurements of radiation quality factor on Mars with the Mars Science Laboratory Radiation Assessment Detector. (August 2019) - Zeitlin, C.; Hassler, D.M.; Ehresmann, B.; Rafkin, S.C.R.; Guo, J.; Wimmer-Schweingruber, R.F.; Berger, T.; Matthiä, D.
Abstract: We report the first long-term measurements of the radiation quality factor of energetic charged particles on the surface of Mars. The Radiation Assessment Detector (RAD) aboard the Mars Science Laboratory rover, also known as Curiosity, has been operating on Mars since 2012. RAD contains thin silicon detectors that record the ionization energy loss of energetic charged particles. The particles are dominantly galactic cosmic rays (GCRs) and the products of their interactions in the Martian atmosphere, with occasional contributions from solar energetic particles (SEPs). The quality factor on the surface of Mars is influenced by two factors: variations in the shielding provided by the atmosphere, and changes in the spectrum of the incident energetic particle flux due to the 11-year solar cycle. The two cannot be easily disentangled using the data alone, but insights can be gained from calculations and Monte Carlo simulations.